Kemanfaatan, Kemudahan, Kompetensi Penggunaan Teknologi Informasi dan Kinerja Auditor di Masa Pandemi Covid-19 - Utari, I Gusti Ayu Nata Dewi; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2024)
The Covid-19 pandemic has led to the implementation of Work From Home (WFH). So that the auditor must be able to implement a new audit pattern by maximizing information technology. This study aims to determine whether there is an effect of the usefulness, ease of use and competence in using information technology on auditor performance during the Covid-19 pandemic. The theory in this research is the Technology Acceptance Model (TAM) Theory. This research was conducted at 7 public accounting firms in Denpasar City which are actively registered with OJK. The number of samples is 39 auditors, using purposive sampling method. Collecting data using a questionnaire. The analysis technique used is multiple linear regression. It was found that the usefulness and ease of use of information technology had an effect on auditor performance during the Covid-19 pandemic. Competence in using information technology has no effect on auditor performance during the Covid-19 pandemic. Improving auditor performance during the Covid-19 pandemic can be done by increasing confidence in the benefits and ease of use of information technology. The level of competence has no impact on the performance of the auditors, especially during the Covid-19 pandemic. Keywords: Usefullness; Ease of Use; Competence; Auditor Performance